Perturbative correction to the adiabatic approximation for (d, p) reactions. (5th August 2021) - Moschini, L; Timofeyuk, N K; Johnson, R C
Abstract: The adiabatic distorted wave approximation (ADWA) is widely used by the nuclear community to analyse deuteron stripping ( d, p ) experiments. It provides a quick way to take into account an important property of the reaction mechanism: deuteron breakup. In this work we provide a numerical quantification of a perturbative correction to this theory, recently proposed in Johnson (2014 J. Phys. G: Nucl. Part. Phys. 41 094005) for separable rank-one nucleon–proton potentials. The correction involves an additional, nonlocal, term in the effective deuteron–target ADWA potential in the entrance channel. We test the calculations with perturbative corrections against continuum-discretized coupled channel predictions which treat deuteron breakup exactly.